STRENGTHENING PRODUCT QUALITY AS A BASIC PRINCIPLE IN BUSINESS - Siti Rodiah (Universitas Pamulang, 2022)
Quality is a guarantee for the existence of a business, even quality is the main requirement in long-term strategic planning. The reason is, quality or quality is the value that consumers need, and in return, consumers will always buy the product or service being sold. In principle, this research focuses on the study of product quality which has implications for loyalty with satisfaction as an intervening. The scientific method used in describing, interpreting, and drawing conclusions is based on quantitative. The analysis technique uses multiple linear regression statistics, which in its operation uses data from the distribution of questionnaires. Sampling was done at simple random to 97 consumers of PT. Kobe Main Cuisine. The results of the study explain that the quality of a product affects consumers' emotions, which then results in feelings of pleasure or satisfaction, from these positive feelings, an experience is built that directs consumers to always make repeated purchases. Interestingly, the research results show that loyalty is very likely to occur if satisfaction is built through product quality.Keywords: Product Quality, Satisfaction, Loyalty, Business Fundamentals